(untitled) (KONFERENSIYA, 2026)
In this article, the author explores the theory of creativity, its criteria, and the effective influence of creativity on the educational process. The study also examines the limitations in developing emotional creativity during language learning and investigates the essence of creativity. Furthermore, the main components of emotional creativity are explained in connection with the educational process. The necessity of creativity in education is substantiated with clear examples.